ANALISIS KONTRIBUSI SEKTOR PERDAGANGAN TERHADAP PRODUK DOMESTIK REGIONAL BRUTO (PDRB) DI KABUPATEN BERAU: ANALISIS KONTRIBUSI SEKTOR PERDAGANGAN TERHADAP PRODUK DOMESTIK REGIONAL BRUTO (PDRB) DI KABUPATEN BERAU - IRA INDRIANI (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2021)
The purpose of this research is to determine the contribution of the education service sector to the gross regional domestic product in Berau Regency, so that it can assist the Berau Regency government ini making programs and policies in the future.In this study using secondary data or publication data obtained from the Central Bureau of statistics of Berau Regency using data analysis, namely contribution analysis. With data for the 2015-2019 period of Berau Regency.The contribution of the Trade Sector to Gross Regional Domestic Product in 2015 was at 5.75 percent, while in 2016 there was an increase from the previous year, namely 5.89 percent. This is due to an increase in trade income in Berau Regency. In 2017 again experienced an increase of 6.02 percent. Then in 2018 there was an increase in the value of its contribution at6.27 percent, in 2019 the value of its contribution was at 6.18 percent. The contribution of the trade sector in 2019 was delayed, this was because trade in line with agriculture and industry experienced growth due to the assumption that some products were traded.